SAT0128 Patterns of cognitive impairment in behÇet's disease. (1st June 2001) - Triolo, G; Monastero, R; Lopez, G; Mannino, M; Ferrante, A; Ciccia, F; Giardina, E; Camarda, R
Abstract : Background: Cognitive dysfunction is a common finding in patients with Behçet's disease. Objectives: The pattern of neuropsychological dysfunction in patients with Behçet's disease (BD) was examined. The influence of current or past clinically overt central nervous system involvement, disease activity, corticosteroid use, HLA B51 allele, and anxiety and depression levels were evaluated. Methods: Twenty-two BD patients fulfilling the criteria of the International Study Group for Behçet Disease, and twenty-two healthy controls, similar for age, gender and education were included in the study. Patients and controls underwent to a standardised battery of neuropsychological and psychological tests. Disease activity was assessed by using the Behçet Current Activity Index (BCAI). The current daily dosage of prednisone (mg/day) was recorded. Results: Cognitive impairment was identified in 41.0% (9) of patients with BD (p < 00008 vs. control). A significantly greater proportion of patients with BD than controls was impaired in tasks assessing attention, episodic memory, semantic and visuospatial abilities (P from < 0.05 to < 0.005). As concern psychological distress BD subjects were significantly more anxious (P < 0.005) and depressed (P < 0.01) than healthy controls. The presence of current or past clinically overt central nervous system involvement, current steroid medication, disease activity, HLA B51 positivity, and psychological distress could not account for these findings. Conclusion: Cognitive dysfunction is a common finding in BD patients. Our series suggest that BD can be associated with a specific pattern of cognitive deficit, involving mainly long-term verbal and visuospatial abilities.